Salas naturales de lectura “una estrategia para fortalecer la competencia lectora” (2019)
The following article, arises from the reflection of the research “Natural Reading Rooms - A strategy to strengthen reading competence” part of the Master in Education Deepening modality of the Pedagogical and Technological University of Colombia, the general objective was to strengthen the reading competence through the implementation of natural reading rooms with the fifth grade students of the Tomás Vásquez Rodríguez Technical Educational Institution from Paipa in the Sativa and la Bolsa Headquarters. This research was framed within the qualitative approach because it was sought to describe from the creation of natural reading rooms, conceived as a novel and attractive space, where nature is the classroom and the learning environment is created from reading. Within an Action Research design, workshops were implemented where students are integrated with environmental education, seeking to develop Eco-critical thinking. Initially, the causes of the low reading and writing rates in the students were identified, in order to design and implement the natural reading rooms. As a conclusion, the natural reading rooms represent a strategy to strengthen the reading communicative competence, promoting the reading habit to project the students as future readers, interested in reading, who enjoy it in a natural and free environment, infecting students wth the love for reading and taking advantage of all the learning capacity.